The Effect of Emotional Intelligence, Job Satisfaction, and Professional Identity on Secondary Teachers’ Engagement - John Kenneth T. Meradios; Charlene C. Alcantara (East Asian Journal of Multidisciplinary Research, 2023)
Teacher engagement and the factors affecting it have been studied previously, but a limited number of studies have investigated structural models. This study used the partial least squares structural equation modeling (PLS-SEM) approach to examine the effects of emotional intelligence, job satisfaction, and professional identity on teacher engagement. An online survey was carried out with a sample of 92 secondary teachers across Nueva Ecija, Philippines. WarpPLS 7.0 was used to analyze the measurement and structural models. The results indicated that emotional intelligence and job satisfaction affect teacher engagement. This study proposes a structural model with meaningful predictive accuracy that can be used as the basis for reformulating or formulating programs to improve teacher engagement.